IRS Attention - BOZANIC, ZAHN; HOOPES, JEFFREY L.; THORNOCK, JACOB R.; WILLIAMS, BRADEN M. (Journal of Accounting Research, 2017)
We study how public and private disclosure requirements interact to influence both tax regulator enforcement and firm disclosure. To capture IRS enforcement activities, we introduce a novel data set of IRS acquisition of firms’ public financial disclosures, which we label IRS attention. We examine the implementation of two new disclosure requirements that potentially alter IRS attention: FIN 48, which increased public tax disclosure requirements, and Schedule UTP, which increased private tax disclosure. We find that IRS attention increased following FIN 48 but subsequently decreased following Schedule UTP, consistent with public and private disclosure interacting to influence tax enforcement. We next examine how private tax disclosure requirements under Schedule UTP affected firms’ public disclosure responses. We find that, following Schedule UTP, firms significantly increased the quantity and altered the content of their tax-related disclosures, consistent with lower tax-related proprietary costs of disclosure. Our results suggest that changes in SEC disclosure requirements altered the IRS's behavior with regard to public information acquisition, and, relatedly, changes in IRS private disclosure requirements appear to change firms’ public disclosure behavior.